Environmental versus geographical determinants of genetic structure in two subalpine conifers. Issue 1 (16th September 2013) - Mosca, Elena; González‐Martínez, Santiago C.; Neale, David B.
Summary Alpine ecosystems are facing rapid human‐induced environmental changes, and so more knowledge about tree adaptive potential is needed. This study investigated the relative role of isolation by distance (IBD) versus isolation by adaptation (IBA) in explaining population genetic structure in Abies alba and Larix decidua, based on 231 and 233 single nucleotide polymorphisms (SNPs) sampled across 36 and 22 natural populations, respectively, in the Alps and Apennines. Genetic structure was investigated for both geographical and environmental groups, using analysis of molecular variance (AMOVA). For each species, nine environmental groups were defined using climate variables selected from a multiple factor analysis. Complementary methods were applied to identify outliers based on these groups, and to test for IBD versus IBA. AMOVA showed weak but significant genetic structure for both species, with higher values in L. decidua. Among the potential outliers detected, up to two loci were found for geographical groups and up to seven for environmental groups. A stronger effect of IBD than IBA was found in both species; nevertheless, once spatial effects had been removed, temperature and soil in A. alba, and precipitation in both species, were relevant factors explaining genetic structure. Based on our findings, in the Alpine region, genetic structure seems to be affected by both geographical isolation and environmental gradients, creating opportunities for local adaptation.